2005
DOI: 10.1140/epjc/s2005-02192-2
|View full text |Cite
|
Sign up to set email alerts
|

Deconfinement and quarkonium suppression

Abstract: Abstract. Modifications in the production pattern of heavy quark bound states have long been considered to provide sensitive signatures for the thermal properties of dense matter created in heavy ion collisions. The original concept of Matsui and Satz for quarkonium suppression as signature for deconfinement in heavy ion collisions has been challenged recently through lattice studies of spectral functions, which indicate the persistence of heavy quark bound states at temperatures well above the transition, as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
29
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 37 publications
7
29
0
Order By: Relevance
“…From the lattice QCD study on the stability of heavy flavor quarkonium in QGP, J/ψ can survive till the temperature 1.6 T c where T c is the critical temperature for the deconfinement phase transition of the system. 2,3 Many other theoretical studies have also shown similar results as well. 4,5 One effective probe of the produced hot medium in heavy ion collisions is the heavy flavor production.…”
Section: Introductionsupporting
confidence: 68%
“…From the lattice QCD study on the stability of heavy flavor quarkonium in QGP, J/ψ can survive till the temperature 1.6 T c where T c is the critical temperature for the deconfinement phase transition of the system. 2,3 Many other theoretical studies have also shown similar results as well. 4,5 One effective probe of the produced hot medium in heavy ion collisions is the heavy flavor production.…”
Section: Introductionsupporting
confidence: 68%
“…The J/ψ is a particularly sensitive probe of the early stages because its survial probability depends on the environment. Lattice gauge theory calculations have indicated that J/ψs do exist above the critical temperature [8,9].The J/ψ suppression was first proposed as a direct signature to identify the QGP formation twenty years ago [10]. Besides the normal suppression induced by nuclear absorption, the J/ψs initially produced by hard processes are anomalously suppressed [11,12,13,14,15,16,17] by interactions in the hot medium.…”
mentioning
confidence: 99%
“…The J/ψ is a particularly sensitive probe of the early stages because its survial probability depends on the environment. Lattice gauge theory calculations have indicated that J/ψs do exist above the critical temperature [8,9].…”
mentioning
confidence: 99%
“…The ratios of high-order cumulants (from the 3rd to the 6th order ones) of conserved quantities are suggested as sensitive measurements of the QCD phase transition [1,2,3,4,5,6,7,8]. Recently, the ratios of low-order cumulants (from the 1st to the 3rd order ones) are turned out to be a useful probe of freeze-out temperatures [9,10]. So it is important to precisely determine the cumulants experimentally, and subtract the influence of non-critical effects.…”
Section: Introductionmentioning
confidence: 99%